ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN BATIK SAJI PACITAN - Fasdian, Frinda; Triyanto, Triyanto; Adelina, Nina (Riset Manajemen dan Akuntansi, 2019)
One of the businesses of Micro, Small and Medium Enterprises (MSMEs) that is growing rapidly in the city of Pacitan, namely Batik, especially Batik Saji Pacitan. Batik Saji, which was founded in 1990, is always crowded with visitors and buyers every day. Various batik fabrics are sold at varying prices. But the impact of increasingly intense business competition in the city of Pacitan, especially competition from similar companies (batik), is also felt by Batik Saji, because competitors also offer relatively cheaper prices and with their respective characteristics, making the Batik Saji company increasingly demanded to move faster in terms of attracting consumers or customers. Key word:Micro, Small and Medium Enterprise, Price, Quality and Place